Media Technology and Motivation for Arabic Learning: A Review of the Literature at a Child’s Age - Ilma Yunita; Nur Najwa; Seri Reski Norma Nensi; Kamisal; Muhammad Faiz Adiyaksa; Besse Mutmainnah; Hamzah Harun Al-Rasyid; Syamsuddin Semmang (Universitas Al-Amien Prenduan, 2026)
Despite the importance of early language acquisition, many educational practices still rely on conventional rote memorization, which often fails to engage young learners. Psychologically, children in the concrete operational stage require visual and interactive stimulation to build interest, especially when learning a foreign language perceived as complex, such as Arabic. To address this challenge, this research aims to analyze the use of technological media to enhance motivation to learn Arabic among children. The method employed in this study is a Systematic Literature Review (SLR), with primary data sourced from the SINTA and Scopus databases within the 2021–2026 timeframe. The PRISMA protocol was used to select journal articles relevant to the inclusion criteria, focusing on subjects aged 7–12 years and indicators of learning motivation. The results indicate that technological media such as educational games, animated videos, and interactive audiovisual applications effectively meet children’s developmental needs in both cognitive and affective domains. These tools provide cognitive scaffolding that transforms abstract linguistic concepts into observable experiences. Consequently, the use of such technology has been shown to increase student engagement and enthusiasm significantly compared to traditional methods. The conclusion emphasizes that selecting technological media aligned with developmental psychology is a key factor in the successful early internalization of Arabic. Keywords: Technological Media, Learning Motivation, Arabic Language, Child Developmental Psychology, Literature Study.